2018
DOI: 10.1142/s0217590818500108
|View full text |Cite
|
Sign up to set email alerts
|

Traceability Information and Willingness to Pay: The Case of Pork

Abstract: Willingness to pay (WTP) for pork with different traceability information was investigated in 143 consumers in Wuxi, Jiangsu Province, China, using experimental auctions combined with real choice experiments based on incentive compatibility and external validity of non-hypothetical elicitation. The results indicated that participants had the highest WTP for government certification information, attached the greatest importance to farming information and comprehensive traceability information on the whole. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Estos resultados implican que la The reference of the origin of the seed (creole or modified) provides information on the traceability of the product, which can be a determining factor for the consumer's willingness to pay an additional price for the corncob. This coincides with the works published by Liu et al (2019), Lu et al (2020) and Xu et al (2019), who found that consumers in various countries are generally willing to pay an additional price for the traceability attribute.…”
Section: Cuadro 5 Modelo Econométrico De La Disposición a Pagar Extrsupporting
confidence: 90%
See 1 more Smart Citation
“…Estos resultados implican que la The reference of the origin of the seed (creole or modified) provides information on the traceability of the product, which can be a determining factor for the consumer's willingness to pay an additional price for the corncob. This coincides with the works published by Liu et al (2019), Lu et al (2020) and Xu et al (2019), who found that consumers in various countries are generally willing to pay an additional price for the traceability attribute.…”
Section: Cuadro 5 Modelo Econométrico De La Disposición a Pagar Extrsupporting
confidence: 90%
“…La referencia del origen de la semilla (criolla o modificada) proporciona información sobre la trazabilidad del producto, lo cual puede ser un factor determinante para la disposición del consumidor a otorgar un sobreprecio al elote, como lo reportado por Liu et al (2019), Lu et al (2020) y Xu et al (2019), quienes encontraron que los consumidores de varios países generalmente están dispuestos a pagar una prima por el atributo de trazabilidad.…”
Section: Cuadro 5 Modelo Econométrico De La Disposición a Pagar Extrunclassified
“…The establishment of a pork traceability system can significantly improve the ability of pig purchasers and sellers, pig slaughtering enterprises, pork sellers, and pork consumers to trace back to pig farm households, which helps to strengthen the regulatory and reputation incentives brought to regulate the safety behavior of pig farm households [35]. In reality, the key to the role of safety assurance is to make pig farm households recognize that their pig farms are involved in the pork traceability system, and this directly depends on government efforts, such as use of ear-tags, use of record-keeping, and quarantine certificate acquisition [34,52]. The above two aspects will increase pig farm households' trust in traceability capabilities, make them aware of the risks and costs of illegal activities, and thus regulate their safety behavior.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…However, the practical implementation and potential challenges of such Islamic-oriented sharecropping arrangements are not adequately addressed in the existing literature. The implications of applying Muzaraah or Mukhabarah principles to sharecropping, the potential benefits and limitations, and how they can address contemporary agricultural challenges remain under-explored [16].…”
Section: Introductionmentioning
confidence: 99%